Comparing user acceptance factors between research software and medical software using AHP and Fuzzy AHP - Mohamadali, Noor Azizah; Garibaldi, Jonathan (2011)
This paper presents a comparison of factors which influence user acceptance of two different types of software. These are research related software and medically related software. Evaluation of user acceptance is crucial because success or failure of any technology depends on the acceptance by the users of the technology. The case studies are conducted to identify if there exist variations in the user acceptance of the software technology factors. In order to assign weights between the factor so that factors can be ranked according to these weights, two multi-criteria decision analysis methods, AHP and Fuzzy AHP, are used. The results demonstrate that for research related software, performance expectancy is the most influential factor of user acceptance. On the other hand, for medical related software, information quality is the most influential factor. We conclude that different types of software technology have different factors that influence user acceptance.